2021
DOI: 10.1002/ecs2.3771
|View full text |Cite
|
Sign up to set email alerts
|

Forest disturbance and arthropods: small‐scale canopy and understory disturbances alter movement of mobile arthropods

Abstract: Dispersal of ground-dwelling arthropods is understudied in forest ecosystems, which hinders understanding of effects of disturbances on population dynamics. The objective of the study was to quantify movement of ground-dwelling arthropods in response to a factorial combination of canopy gap formation via girdling and understory vegetation removal, which was shown in a companion study to alter arthropod abundance and species richness. Arthropod movement was quantified using a self-mark-capture technique where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Accordingly, the bamboo spread has the potential to modify the microclimate of the forest floor (Araujo, 2008; Griscom et al, 2013; Rother et al, 2016) by increasing the soil temperature and diminishing the soil moisture (Collins et al, 1985; Fahey & Puettmann, 2007; Gray et al, 2002; Ishizuka et al, 2002; Perry & Herms, 2016). These modifications may create more diverse and suitable niches for arthropods (Perry et al, 2021), thus increasing their abundance and richness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the bamboo spread has the potential to modify the microclimate of the forest floor (Araujo, 2008; Griscom et al, 2013; Rother et al, 2016) by increasing the soil temperature and diminishing the soil moisture (Collins et al, 1985; Fahey & Puettmann, 2007; Gray et al, 2002; Ishizuka et al, 2002; Perry & Herms, 2016). These modifications may create more diverse and suitable niches for arthropods (Perry et al, 2021), thus increasing their abundance and richness.…”
Section: Discussionmentioning
confidence: 99%
“…Litter‐dwelling arthropods contribute significantly to the arthropod diversity in tropical forests (Bardgett et al, 2005; Novotny et al, 2006; Stork & Grimbacher, 2006), and play a key role in ecosystem functions such as nutrient cycling and carbon sequestration (Costanza et al, 2017; deVries et al, 2013; Jeffery et al, 2010). They are well‐known drivers of many functions in forest ecosystems and are influenced by natural/semi‐natural disturbances (fire, invasion, etc.,) and forest management activities (logging, harvesting and restoration), emphasising their pivotal role as bio‐indicators in monitoring forest health (Hartshorn, 2021; Oliver et al, 2000; Perry et al, 2021). Litter‐dwelling arthropods are involved in the primary decomposition that facilitates the subsequent microbial breakdown of organic matter (Cardenas et al, 2017; Grandy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Alejandro et al [48] showed that microhabitat destruction and large reductions in lower trophic level species caused by rainfall can make it difficult for predatory functional taxa and soil invertebrates with poor dispersal abilities (e.g., ants and spiders) to survive. In contrast, soil invertebrates with a high dispersal capacity (e.g., beetles) are slightly affected by rainfall [49], and these mobile populations are able to expand their ranges [50] and travel to additional areas to access food resources [51]. We also found that the population density of predators, i.e., Coleoptera and Lepidoptera insects, in CF and SF was higher than that in MF and BF and significantly decreased during the typhoon disturbances (Table S1), which undoubtedly confirms our idea.…”
Section: The Short-term Response and Restoration Of Soil Invertebrate...mentioning
confidence: 99%
“…In some cases, researchers can compromise by using a few tracking devices with a risk of reduced data quantity and subsequent problems with publishing. This obstacle can be partially overcome by using relatively low‐budget methods, such as direct observation (Drees et al, 2008; Cerda et al, 2015), capture‐mark‐recapture (Kagawa & Maeto, 2009; Svensson et al, 2011), or fluorescent powder applied on the ground (Perry et al, 2021). Unfortunately, these approaches have considerable limitations for obtaining detailed movement data suitable for trajectory analyses.…”
Section: Radio Telemetry As a Tool For Studying Beetle Movementmentioning
confidence: 99%